2019
DOI: 10.1001/jamanetworkopen.2019.8686
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Host Immune Response Trajectories Among Hospitalized Patients With Sepsis

Abstract: This multicenter cohort study of adults who have survived hospitalization for sepsis assesses whether abnormalities in the host immune response during hospitalization for sepsis persist after discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
112
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(120 citation statements)
references
References 20 publications
5
112
0
3
Order By: Relevance
“…The 1-year mortality rate among sepsis survivors in the present study is within the range previously reported in the literature. 9,16,36 Shankar-Hari et al 16 and Yende et al 36 recently reported 1-year mortality rates of 15% and 17.6%, respectively, among relatively young and previously healthy patients with few comorbidities and high rates of prehospital functional independence. In contrast,…”
Section: Discussionmentioning
confidence: 99%
“…The 1-year mortality rate among sepsis survivors in the present study is within the range previously reported in the literature. 9,16,36 Shankar-Hari et al 16 and Yende et al 36 recently reported 1-year mortality rates of 15% and 17.6%, respectively, among relatively young and previously healthy patients with few comorbidities and high rates of prehospital functional independence. In contrast,…”
Section: Discussionmentioning
confidence: 99%
“…We and others have highlighted that 1 in 2 sepsis survivors have unplanned rehospitalizations or die in the first year after hospital discharge. 19 , 29 , 30 , 31 Currently, the follow-up care of sepsis survivors is neither risk based nor uniform within and between health care systems. Seldom does every sepsis survivor receive follow-up care.…”
Section: Discussionmentioning
confidence: 99%
“…In hospital survivors, failure to achieve homeostatic correction has a significant negative long-term impact, with experimental work suggesting that it might potentiate the peripheral and brain pro-inflammatory cytokine response to a subsequent inflammatory challenge (44). Independently of age and comorbidities, patients with elevated circulating biomarkers of inflammation and hemostasis at hospital discharge have persistent elevation over time with increased risk for cardiovascular events, re-hospitalizations, and 1-year mortality (41,45,46). "Persistent Inflammation, Immunosuppression, and Catabolism Syndrome" (PICS) has been postulated as the underlying pathophysiology of chronic critical illness (CCI) (18,47).…”
Section: Innate Immunity and Nuclear Factor-κbmentioning
confidence: 99%